Azithromycin and Ciprofloxacin Treatment Outcomes During an Outbreak of Multidrug-Resistant Shigella sonnei Infections in a Retirement Community—Vermont, 2018. (16th May 2021) - Gharpure, Radhika; Friedman, Cindy R; Fialkowski, Veronica; Collins, Jennifer P; Strysko, Jonathan; Marsh, Zachary A; Chen, Jessica C; Meservey, Elizabeth H; Adediran, Azizat A; Schroeder, Morgan N; Wadhwa, Ashutosh; Fullerton, Kathleen E; et al.
Abstract: Background: In 2018, the Centers for Disease Control and Prevention and the Vermont Department of Health investigated an outbreak of multidrug-resistant Shigella sonnei infections in a retirement community that offered a continuum of care from independent living through skilled nursing care. The investigation identified 24 culture-confirmed cases. Isolates were resistant to trimethoprim-sulfamethoxazole, ampicillin, and ceftriaxone, and had decreased susceptibility to azithromycin and ciprofloxacin. Methods: To evaluate clinical and microbiologic response, we reviewed inpatient and outpatient medical records for treatment outcomes among the 24 patients with culture-confirmed S. sonnei infection. We defined clinical failure as diarrhea (≥3 loose stools per day) for ≥1 day after treatment finished, and microbiologic failure as a stool culture that yielded S. sonnei after treatment finished. We used broth microdilution to perform antimicrobial susceptibility testing, and whole genome sequencing to identify resistance mechanisms. Results: Isolates contained macrolide resistance genes mph(A) and erm(B) and had azithromycin minimum inhibitory concentrations above the Clinical and Laboratory Standards Institute epidemiological cutoff value of ≤16 µg/mL. Among 24 patients with culture-confirmed Shigella infection, 4 were treated with azithromycin; all had clinical treatment failure and 2 also had microbiologic treatment failure. Isolates were susceptible to ciprofloxacin but contained a gyrA mutation; 2 patients failed treatment with ciprofloxacin. Conclusions: These azithromycin treatment failures demonstrate the importance of clinical breakpoints to aid clinicians in identifying alternative treatment options for resistant strains. Additionally, these treatment failures highlight a need for comprehensive susceptibility testing and systematic outcome studies, particularly given the emergence of multidrug-resistant Shigella among an expanding range of patient populations. Abstract : Among 24 patients in a multidrug-resistant Shigella outbreak, 4 were treated with azithromycin; all had clinical treatment failure (persistent diarrhea) and 2 also had microbiologic failure (stool culture yielding Shigella sonnei ). Additionally, 2 patients failed treatment with ciprofloxacin (1 clinical, 1 microbiologic).